LC–MS/MS-QTOF analysis of Anodendron parviflorum (Roxb.) leaves extract and exploring its antioxidant, antimicrobial, and cytotoxic potential - Sharmila, Arunagiri; Selvaraj, Chinnadurai Immanuel (Future journal of pharmaceutical sciences, 2024)
Background Traditional medicine claims that Anodendron parviflorum has benefits for treating various human diseases. The present study seeks to understand better the phytochemical and LC–MS/MS-QTOF profiling of A. parviflorum 's ethanolic extract and to investigate the properties of the different solvents of A. parviflorum for anti-inflammatory, antioxidant, antimicrobial, toxicity, and cytotoxic effects. Results The quantitative methods exhibited higher total phenolics (327.16 ± 2.4 mg GAE/g dw), total flavonoid (109.82 ± 1.9 mg QE/g dw), and total alkaloid (14.13 ± 0.09%) content in ethanol extract. In contrast, a higher total extraction value (22.8 ± 0.6%) and total terpenoid (57.23 ± 0.06 mg LL/g dw) content was shown in the methanol extract of A. parviflorum . LC–MS/MS-QTOF analysis of its ethanolic extract revealed a notable occurrence of phenols and flavonoids. The ethanolic extract of A. parviflorum exhibited significant antioxidant activities with lower IC 50 values in DPPH, phosphomolybdenum, and metal chelating and reducing power assay. The methanolic extract of A. parviflorum had the more significant anti-inflammatory property (94.55 ± 0.1%) in the bovine serum albumin assay. The extracts also demonstrated a higher inhibition zone against pathogenic bacteria. The ethanolic extract of A. parviflorum demonstrated substantial cytotoxicity against A549 cells. Conclusion Consequently, these findings validate the use of A. parviflorum in traditional medical practices due to its bioactive compounds, which may have potential therapeutic value in various biomedical applications. Highlights A. parviflorum leaves extract showed the presence of significant levels of alkaloids, flavonoids, phenols, and terpenoids. LC–MS/MS-QTOF analysis revealed notable bioactive compounds of A. parviflorum. The different extracts showed remarkable antioxidant and antimicrobial activities. The extracts exhibited less hemolytic and higher thrombolytic activities. It demonstrated significant cytotoxicity against A549 cell lines. Graphical abstract